Absorption of Organic Molecules on Alkali Metal-Graphite Intercalation Compounds - Ogawa, Ayumi; Takahashi, Yoichi; Sakuno, Hidekazu; Akuzawa, Noboru (TANSO, 1990)
Effects of starting carbon material (Heat-Treatment Temperature, 1000, 1500, 2000 and 2600°C) and chemical composition of K-GICs on the absorption of tetrahydrofuran (THF) and benzene (Bz) on potassium-graphite intercalation compounds (K-GICs) have been investigated by gravimetry and X-ray diffraction measurements. It is found that THF is absorbed on K-GICs, irrespective of the starting carbon material. On the contrary, benzene absorption is very sensitive to the degree of graphitization of the starting carbon material: No absorption was observed, except for K-GICs prepared from HTT-2600 carbon material. It is also found that as the composition of K-GICs, K/C, decreases, the absorbed amount, M/K (M denotes THF and benzene), increases. It is considered that the decrease of K/C results in the increase of interlayer free volume, where molecules are accomodated. Absorption of thiophene on cesium-graphite intercalation compounds (Cs-GICs) and on K-GICs prepared from natural graphite flakes were also investigated. Isotherms and effect of composition of Cs-GICs are determined.